Analysis of the cell fusion activities of chimeric simian immunodeficiency virus-murine leukemia virus envelope proteins: inhibitory effects of the R peptide. - Yang, C (1996)
It was previously reported that truncation or proteolytic removal of the C-terminal 16 amino acids (the R peptide) from the cytoplasmic tail of the murine leukemia virus (MuLV) envelope protein greatly increases its fusion activity. In this study, to investigate the specificity of the effect of the R peptide on the fusion activity of viral envelope proteins, we expressed simian immunodeficiency virus (SIV)-MuLV chimeric proteins in which the entire cytoplasmic tail of the SIV envelope protein was replaced by either the full-length MuLV cytoplasmic tail or a truncated MuLV cytoplasmic tail with the R peptide deleted. Extensive fusion of CD4-positive cells with the chimeric protein containing a truncated MuLV cytoplasmic tail was observed. In contrast, no cell fusion activity was found for the chimeric protein with a full-length MuLV cytoplasmic tail. We constructed another SIV-MuLV chimeric protein in which the MuLV R peptide was added to an SIV envelope protein cytoplasmic tail 17 amino acids from its membrane-spanning domain. No fusion activity was observed within this construct, while the corresponding truncated SIV envelope protein lacking the R peptide showed extensive fusion activity. No significant difference in the transport or surface expression was observed among the various SIV-MuLV chimeric proteins and the truncated SIV envelope protein. Our results thus demonstrate that the MuLV R peptide has profound inhibitory effects on virus-induced cell fusion, not only with MuLV but also in a distantly related retroviral envelope protein which utilizes a different receptor and fuses different cell types.